Is there a connection between circadian type and seasonal affective disorder in Iceland? - Katla Sigurðardóttir 1993-; Grigaraviciuté, Giedré, 1991- (2019)
Seasonal affective disorder (SAD) is a combination of natural and mood disturbances with a seasonal pattern, typically occurring in the autumn and winter with a decrease of symptoms in the spring or summer (Kurlansik et al. 2012). In Iceland there is on average more darkness than sunlight, counting up to 1268.4 hours of sunlight, throughout the year (Veðurstofa Íslands. 2007). A circadian rhythm is a biological rhythm found in humans and animals that occur repeatedly and are in excellent coordination of biological systems and adjustment to the living environment. Turpin (1992) indicated that there are two circadian types of humans, either morning or evening types. Here we investigated the possible connection between circadian types and seasonal affective disorder in Iceland and the interaction of those results with age and gender in the population. Six psychological questionnaires used, where three of them already had an Icelandic translation those were the Depression Anxiety Stress Scales (DASS), Patient Health Questionnaire-9 (PHQ-9) and the Seasonal Pattern Assessment Questionnaire (SPAQ). The authors along with their team members did the Icelandic translation for the remaining three questionnaires: the Bergen Insomnia Scale (BIS), The Movement Imagery Questionnaire (MIQ) and Morningness-Eveningness Questionnaire (MEQ). In this study, there were 241 participants after the exclusion of missing data, recruited in February in public places such as libraries, golf clubs, and workplaces, as well as over the internet. They were grouped by age in young (18-29), middle (30-59), and old (60+). A Pearson's Chi-squared test showed a relationship between circadian type and SAD (x^2(2) = 9.235, p-value = 0.009878) and according to the binomial logistic regression the evening vs. morning chronotype had the most substantial influence on SAD (z= 2.097, p= 0.036) while none of the other variables, age or gender, were significant. Evening chronotype is more vulnerable to seasonal changes than other chronotypes, concluding that ...